The economic security index: A new measure for research and policy analysis - Jacob S. Hacker; Gregory Alain Huber; Austin Nichols; Philipp Rehm; Mark J. Schlesinger; Robert G. Valletta; Stuart Craig (Institute for the Study of Labor (IZA), 2012)
This paper presents the Economic Security Index (ESI), a new, more comprehensive measure of economic insecurity. By combining data from multiple surveys, we create an integrated measure of volatility in available household resources, accounting for fluctuations in income and out-of-pocket medical expenses, as well as financial wealth sufficient to buffer against these shocks. We find that insecurity has risen steadily since the mid-1980s for virtually all subgroups of Americans, albeit with cyclical ups and downs. We also find, however, that there is substantial disparity in the degree to which different groups are exposed to economic risk. As the ESI derives from a data-independent conceptual foundation, it can be measured using different data sources. We find that the degree and disparity by which insecurity has risen is robust across these sources.
Keywords: I14; D31; J11; 330; household income; volatility; wealth; medical spending; Privater Haushalt; Risiko; Sozialer Indikator; Haushaltseinkommen; Volatilität; Vermögen; Gesundheitskosten; USA